Prednisolone enhances beta-cell function independently of ambient glycemic levels in type II diabetes. - Hosker, J; Burnett, M; Matthews, DR; Turner, R (1993)
This study examined the changes in beta-cell response and insulin sensitivity induced by a single overnight dose of 15 mg prednisolone in eight type II diabetic subjects, seven nondiabetic normal controls, and eight subjects with a first-degree type II diabetic relative who were therefore at risk of developing diabetes. beta-Cell secretion was assessed by use of the hyperglycemic clamp technique, and insulin sensitivity was assessed with the clamp and the Continuous Infusion of Glucose with Model Assessment (CIGMA) technique. Subjects were studied in random order on two occasions, after placebo and after prednisolone administration. Normal subjects showed an increase of median fasting glucose level from 4.7 to 5.2 mmol.L-1 after prednisolone (P < .02) and at-risk subjects showed an increase from 4.8 to 5.5 mmol.L-1 (P < .005), whereas diabetic subjects showed no significant increase in median fasting plasma glucose level (7.0 mmol.L-1 after placebo and 6.3 mmol.L-1 after prednisolone). Six of these eight diabetic subjects showed a paradoxical decrease of fasting plasma glucose level after prednisolone therapy. All three groups showed a significant elevation of clamp steady-state plasma insulin levels following prednisolone, with a median percentage elevation of 46%, 66%, and 31% for normal, at-risk, and diabetic subjects, respectively. All three groups showed significant reduction in insulin sensitivity measured by CIGMA following prednisolone of 51%, 41%, and 25% of pre-prednisolone levels in normal, at-risk, and diabetic subjects, respectively, with a significantly greater reduction in normal subjects than in diabetics (P < .02).(ABSTRACT TRUNCATED AT 250 WORDS)